2002
DOI: 10.1105/tpc.006379
|View full text |Cite
|
Sign up to set email alerts
|

Cloning the Tomato Curl3 Gene Highlights the Putative Dual Role of the Leucine-Rich Repeat Receptor Kinase tBRI1/SR160 in Plant Steroid Hormone and Peptide Hormone Signaling

Abstract: Brassinosteroids (BRs) are plant steroid hormones that are essential for normal plant development. To gain better understanding of the conservation of BR signaling, the partially BR-insensitive tomato mutant altered brassinolide sensitivity1 ( abs1 ) was identified and found to be a weak allele at the curl3 ( cu3 ) locus. BR content is increased in both of these mutants and is associated with increased expression of Dwarf . The tomato homolog of the Arabidopsis Brassinosteroid Insensitive1 Leu-rich repeat (LRR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 212 publications
(148 citation statements)
references
References 60 publications
7
136
0
5
Order By: Relevance
“…Mutations of BRI1 orthologs in rice, pea, and tomato cause BR insensitive dwarf phenotypes [37][38][39], suggesting highly conserved function of BRI1. Interestingly, the tomato BRI1 was shown to function as receptor for both BR and systemin, a small peptide involved in plant defense (reviewed by Wang and He, 2004 [40]).…”
Section: Tissue Specific Functions Of the Homologs Of Bri1 And Bak1mentioning
confidence: 99%
“…Mutations of BRI1 orthologs in rice, pea, and tomato cause BR insensitive dwarf phenotypes [37][38][39], suggesting highly conserved function of BRI1. Interestingly, the tomato BRI1 was shown to function as receptor for both BR and systemin, a small peptide involved in plant defense (reviewed by Wang and He, 2004 [40]).…”
Section: Tissue Specific Functions Of the Homologs Of Bri1 And Bak1mentioning
confidence: 99%
“…Additional insights into their functions can be provided by comparative analysis of homologous receptors in another species. For example, the tomato RLK SR160 has been postulated to exhibit dual functionality as receptor for brassinosteroid and systemin (Montoya et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Severe bri1 mutants lacking functional BR receptors show serious developmental defects, such as severe dwarfness, irregular vascularization, and male sterility (Clouse et al 1996;Montoya et al 2002), which have also been observed in BR-deficient plants (Szekeres et al 1996;Li et al 1996;Bishop et al 1996). This indicates the essential role of BRI1 in BR perception.…”
Section: Introductionmentioning
confidence: 77%